The Effects of Head Teacher (Educational Leaders) Vision on Teachers Jobs Satisfaction - Basharat Hussain Sehar; Uzma Nazir; Akhtar Abbas; Badar Zaman; Fahad Bin Khalid (International Journal of Education, Vocational and Social Science, 2024)
This study focused on four decision-making styles i.e., (a) autocratic: where managers do not consult any member of their organization and make final decision alone (b) consultative: where managers get advice from the members of their organization, take it into consideration and make final decision alone (c) democratic: where leader gives up the ownership and control of the decision allowing the group in majority to decide the action, (d) consensus: where the leader gives up total control of the decision; whole group of subordinates is involved in decision-making process and everyone must agree and “buy in” on the decision